Surgical Treatment of an Unusual Ski Injury: Combined Tibial Fracture With Anterior Cruciate Ligament Avulsion and Segond Lesion - Edoardo Monaco MD; Etienne Cavaignac MD, PhD; Natale Criseo MD; Alessandro Annibaldi MD; Matteo Cantagalli MD; Rita Pucciatti MD; Alessandro Carrozzo MD; Andrea Feretti MD (Video Journal of Sports Medicine, 2023)
Background: Alpine skiing is considered to be a high-risk sport due to frequent knee injuries and lower limb fractures. The most common lower limb fracture is tibial shaft fracture, while the most common ligament injuries include anterior cruciate ligament (ACL) or medial collateral ligament tears. An injury rarely described in the literature is the association of a bony leg fracture with an ACL injury and Segond fracture. Indications: While the tibial fracture can be managed with intermedullary nailing and proximal ACL tears can be managed with primary repair, the combination of treatments including fixation of the Segond fracture is uncommon. Technique Description: We report combination treatment with nailing for the tibial fracture, primary repair for the ACL avulsion, and primary fixation of Segond fracture. Results: Simultaneous reduction and fixation of the fracture and stabilization of the knee with ACL and anterolateral ligament repair in a single stage resulted in an excellent outcome with complete healing of tibial fracture, ACL repair, and Segond fixation at final follow-up. Discussion/Conclusion: Even if combined leg fracture associated with ipsilateral ACL tear and Segond fracture is a very rare injury, the described technique based on 1-stage fixation of the 3 injuries is a viable option. This surgical technique can be considered a reparative treatment, with the goal of preserving the joint. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.